Development of dissimilar metal joining method for CP-Ti and SS-316L using gtaw with tin babbitt filler rod - Anugra, Binar Ade; Ramdan, Raden Dadan; Wahyudiono, Wahyudiono (Eastern-European Journal of Enterprise Technologies, 2025)
Dissimilar metal joining between commercial pure titanium (CP-Ti) and stainless steel 316L (SS-316L) poses challenges due to thermal property differences and brittle intermetallic compound formation. This study examines weldability and joint characteristics under varying welding currents (185A, 195A, 205A) and backing plate conditions. The main challenge is ensuring weld integrity while minimizing intermetallic compounds and defects that degrade mechanical properties. Non-destructive testing, metallography, SEM-EDS, and hardness testing were conducted. Results indicate that without a backing plate, hardness in the heat-affected zone (HAZ) of SS-316L increased with welding current, from 160.7 HV at 185 A to 167.5 HV at 205 A. In CP-Ti, hardness rose from 148 HV at 185 A to 160.7 HV at 205 A. With a backing plate, SS-316L HAZ hardness peaked at 185 A (182.7 HV) but decreased to 167.5 HV at 205 A. Similarly, CP-Ti hardness was lower with a backing plate (154 HV at 205 A BP). Sensitization in SS-316L was detected but remained mild. The tin babbitt filler rod suppressed brittle Fe-Ti intermetallic compounds due to its high thermal conductivity and low melting point, ensuring better heat distribution. This reduced cracking risks at the fusion line and improved bonding. However, porosity remained an issue, particularly in SS-316L joints, increasing at higher currents and potentially leading to microcracks. Controlling welding parameters and shielding conditions was crucial to minimizing porosity and enhancing joint quality. These findings confirm that optimizing welding parameters and environmental control reduces intermetallic compounds and porosity, improving GTAW feasibility for on-field welding in applications such as heat exchangers, piping, and pressure vessels